Hibridisasi Seni Kerajinan Patung di Desa Kedisan, Bali - Sutjiati Beratha, Ni Luh; Sukarini, Ni Wayan; Rajeg, I Made (Jurnal Kajian Bali (Journal of Bali Studies); Vol 6 No 2 (2016): RUANG IMAJINER DAN RUANG PUBLIK DI BALI, 2016)
This article discusses Balinese handicraft especially statue handicraft produced by craftsmen at Kedisan Village, Tegal-lalang District, Gianyar Residence. The competitiveness of the product is very high in tourism market and has the process of hybridization. The specific target that will be achieved related to the identity maintenance of Balinese culture. Thus the main discussion of this article is the caused of hybridization on statue handicraft in Bali. In the era of globalization the fusion between local and global cultures has already happened and this is a phenomenon of postmodernism because there is relationship of cultural influences. This condition can be comprehended from hybridization phenomenon on statue handicraft in Bali. Theories of globalization and glocalization are applied to analyse the data in this article. Qualitative method is used to achieve the objective and target through the implementation of participated observation technique and in-depth interview. The whole data is analysed descriptively, holisticly, and interpretatively. The Balinese artists on statue have done the changes in the form of statue through hybridization against the statue as the effect of made to order because of internal and external factors.
Keywords: cultural tourism, Balinese handicraft, hybridization